STUDY OF COASTAL TOURISM DEVELOPMENT IN THE EAST COAST OF NORTH SUMATRA PROVINCE - Hasanah, Uswatun; Ilmi Faried, Annisa; Sembiring, Rahmad (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to describe and analyze the needs of  tourists both the development of infrastructure, the development of the carrying capacity of hospitality, as well as the carrying capacity of the community and local government, The research method used in this study uses the mix method using scoring analysis.  The results of the scoring analysis found that the problems of coastal tourism in the East Coast Region on average were almost the same, namely infrastructure development, hospitality carrying capacity, and local government carrying capacity. So it needs some recommendation proposals. Such as recommendations for the development of infrastructure carrying capacity, namely accelerating improvements and fulfillment of tourism supporting facilities to provide comfort to tourists while traveling, recommendations for the development of hospitality carrying capacity are action plans for assistance in the implementation of the sapta pesona program to the community. Management / institutional strengthening from the community, government and private sector that is effective to manage tourism (Pokdarwis). And recommendations for developing the carrying capacity of the role of local governments preparing regulations to support east coast tourism activities in North Sumatra Province.